Inhibitory Effects and Composition Analysis of Romanian Propolis: Applications in Organic and Sustainable Agriculture - Gabriel Heghedűş-Mîndru; Mirel Glevitzky; Ramona Cristina Heghedűş-Mîndru; Gabriela-Alina Dumitrel; Maria Popa; Ioana Glevitzky; Diana Obiștioiu; Ileana Cocan; Mihaela Laura Vică (Plants)
Propolis is a sustainable and environmentally friendly agrochemical of natural origin, a resinous mixture produced by honeybees. It is used as a natural remedy in multiple pathologies., but it is also a natural defense enhancer, a phytostimulator that helps to bind, bloom, and pollinate plants. Propolis is used in organic farming as a phytoprotector and phytostimulator. The present study investigates the main physical–chemical parameters of Romanian propolis, its antifungal activity against five fungal strains (Aspergillus niger, Aspergillus flavus, Penicillium chrysogenum, Fusarium oxysporum, and Rhizopus stolonifer) and its phyto-inhibitory activity when it is applied on the layer and under the layer for different grain crops (wheat, maize, oats, and barley). Different doses were used—1, 5, and 10 g of propolis powder—and the growth of the plume was monitored for 13 days. The physical–chemical parameters investigated are volatile oils, wax, oxidation index, melting point, dry matter, ash, and resin, and maximum values were obtained for phenols (189.4 mgGAE/g), flavonoids (84.31 mgQE/g), and IC50 (0.086 µg/mL). Propolis demonstrates high antifungal activity against all fungal strains. The results showed that propolis has the best phyto-inhibition potential among the studied grain crops when it is applied on the layer, with the lowest plume growth for maize (14 mm), followed by oats, barley, and lastly wheat (24 mm). Propolis can find increasing application in sustainable and environmentally friendly agriculture and the obtaining of organic food.